TNF-α and Microalbuminuria in Patients with Type 2 Diabetes Mellitus - I.-Th. Lampropoulou; M. Stangou; A. Papagianni; T. Didangelos; F. Iliadis; G. Efstratiadis (Journal of Diabetes Research)
Aim. Recent evidence suggests that chronic subclinical inflammation plays a key role in the pathogenesis and progression of diabetic nephropathy. Aim of the present study was to investigate possible correlation between the presence and degree of microalbuminuria and markers of inflammation in patients with type 2 diabetes mellitus (DM). Patients-Methods. Eighty patients were enrolled and clinical and laboratory data were recorded. Albumin-creatinine ratio (ACR) was calculated in first-morning urine samples. Serum and urinary tumor necrosis factor-α (TNF-α) levels were determined by ELISA. Results. Forty-five patients had normoalbuminuria, 33 microalbuminuria, and 2 macroalbuminuria. Patients with microalbuminuria were older, with higher glycosylated hemoglobin levels (HbA1c) and they more frequently had diabetic retinopathy, neuropathy, and cardiovascular disease and were on treatment with angiotensin converting enzyme inhibitors (ACEi) and/or angiotensin receptor blockers (ARBs). ACR was significantly correlated with the presence of cardiovascular disease, hypertension, and HbA1c levels and the administration of clopidogrel and ACEi or ARBs. ACR was not correlated with C-reactive protein, fibrinogen, or serum TNF-α levels but had a strong correlation with urinary TNF-α levels. Conclusions. In patients with type 2 DM, urinary, but not serum, TNF-α levels are associated with the presence and severity of microalbuminuria.